Decreased sigmoidal ABCB1 (P-glycoprotein) expression in ulcerative colitis is associated with disease activity. (December 2009) - Ufer, Mike; Hääsler, Robert; Jacobs, Gunnar; Haenisch, Sierk; Läächelt, Sandra; Faltraco, Frank; Sina, Christian; Rosenstiel, Philip; Nikolaus, Susanna; Schreiber, Stefan; Cascorbi, Ingolf
Aims: The modulation of the intestinal expression of detoxifying proteins by relevant transcription factors, intracellular receptors and cytokines in ulcerative colitis (UC) is poorly understood. Here, we compared the intestinal expression of drug transporters, metabolizing enzymes and putative regulatory genes between inflamed and noninflamed tissue and studied their modulation by disease activity.Materials & methods: Sigmoidal biopsies of 18 UC patients and 18 healthy volunteers matched for age, gender and ABCB1 3435C >T genotype were investigated for mRNA expression levels of 43 systematically selected candidate genes by low-density array real-time PCR. Additionally, the ABCB1 gene product P-glycoprotein was visualized by immunohistochemistry and quantified by western blotting. Disease phenotype was categorized by clinical, endoscopic and histopathological examination. Disease activity was quantified by clinical activity index.Results: In inflamed sigmoidal tissue from UC patients, 11 genes ( NAT1, NR2B1, CEBPB, IFG, IL8, IL10, S100A12, SPP1, DEFA5, DEFA6 and HAMP ) were overexpressed. By contrast, only the major human efflux transporter ABCB1 showed significantly lower expression levels, that were inversely correlated with those of certain antimicrobial peptides (DEFA5/6) and cytokines (IL1ββ and IL8). Cell culture experiments revealed a time-dependent decrease of ABCB1 expression upon IL8 exposure. Disease activity profoundly modified ABCB1 expression, indicated by an inverse correlation of clinical activity index values with ABCB1 mRNA expression (r = -0.603; p = 0.017) and markedly reduced protein expression in UC patients with moderate and severe symptomology (p = 0.011).Conclusion: Cytokine-mediated downregulation of the major human efflux transporter ABCB1 in inflamed intestine of UC patients is presumably dependent on disease activity, with a possible contribution from IL8.